Coagulations Studies Do Not Correlate With Each Other or With Hematologic Complications During Pediatric Extracorporeal Membrane Oxygenation*. Issue 6 (5th March 2021) - Deshpande, Shyam J.; Vitali, Sally; Thiagarajan, Ravi; Brediger, Steven; McManus, Michael; Geva, Alon
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Anticoagulation plays a key role in the management of children supported with extracorporeal membrane oxygenation. However, the ideal strategy for monitoring anticoagulation remains unclear. Our objective was to evaluate the utility of laboratory measures of anticoagulation in pediatric extracorporeal membrane oxygenation. DESIGN: Retrospective cohort study. SETTING: Quaternary care academic children's hospital. PATIENTS: Children in a noncardiac PICU cannulated to extracorporeal membrane oxygenation in 2010—2016. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Demographic data, laboratory values, and heparin doses were extracted from the enterprise data warehouse. Primary diagnoses, indications for cannulation, hemorrhagic and thrombotic complications, and survival outcomes were abstracted from the local registry used for Extracorporeal Life Support Organization reporting. Statistical models accounting for repeated measures using generalized estimating equations were constructed to evaluate correlations between heparin doses and laboratory values; among laboratory values; and between heparin dose or laboratory values and clinical outcomes. One hundred thirty-three unique patients—78 neonates and 55 older patients—were included in the study. There was no significant association between antifactor Xa level, activated partial thromboplastin time, activated clotting time, or heparin dose with hemorrhage or thrombosis (odds ratio ≅ 1 for all associations). There was weak-to-moderate correlation between antifactor Xa, activated partial thromboplastin time, and activated clotting time in both neonates and older pediatric patients ( R 2 < 0.001 to 0.456). Heparin dose correlated poorly with laboratory measurements in both age groups ( R 2 = 0.010–0.063). CONCLUSIONS: In children supported with extracorporeal membrane oxygenation, heparin dose correlates poorly with common laboratory measures of anticoagulation, and these laboratory measures correlate poorly with each other. Neither heparin dose nor laboratory measures correlate with hemorrhage or thrombosis. Further work is needed to identify better measures of anticoagulation in order to minimize morbidity and mortality associated with extracorporeal membrane oxygenation.